2021
DOI: 10.31631/2073-3046-2021-20-1-44-50
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Methicillin-Resistant Staphylococcus Strains in the Moscow Medical and Surgical Center using Molecular-Biological Methods

Abstract: Relevance. Staphylococci are one of the most common pathogens in the etiological structure of nosocomial infections. Methicillinresistant staphylococci are resistant to the main groups of antibiotics and are one of bacteria that pose the greatest threat to human health according to the World Health Organization. The introduction of modern molecular biological methods in the monitoring of methicillin-resistant staphylococci is necessary for the rapid and accurate identification of microorganisms, monitoring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…A number of S. epidermidis isolates have been previously reported in Russia (https: //pubmlst.org, accessed on 15 September 2021). Among the sequence types identified in this study, the ST5, ST20, and ST23 isolates were found in 2008-2009 in Moscow and Nizhny Novgorod, European Russia, whereas ST786 was obtained from a hospitalized patient in 2018 in Moscow [49]. Others, namely ST17, ST152, and ST210, were found for the first time in Russia.…”
Section: Discussionmentioning
confidence: 57%
“…A number of S. epidermidis isolates have been previously reported in Russia (https: //pubmlst.org, accessed on 15 September 2021). Among the sequence types identified in this study, the ST5, ST20, and ST23 isolates were found in 2008-2009 in Moscow and Nizhny Novgorod, European Russia, whereas ST786 was obtained from a hospitalized patient in 2018 in Moscow [49]. Others, namely ST17, ST152, and ST210, were found for the first time in Russia.…”
Section: Discussionmentioning
confidence: 57%
“…Многими авторами отмечено, что штаммы грамотрицательных и грамположительных микроорганизмов на протяжении десятилетий циркулируют в стационарах, особенно в реанимационных и хирургических отделениях [7][8][9][10].…”
Section: Optimization Of Monitoring Of Nosocomial Infections In Hospi...unclassified
“…The corresponding burden of the US healthcare system was estimated about 10 billion US $ in 2013 [4]. Along with this, the healthcare environment is a reservoir for the cultivation of strains of microorganisms that are resistant to antibiotics and/or disinfectants [5][6][7][8], which further aggravates the multidrug resistance problem. The development of new antibacterial drugs is certainly an extremely important task for global healthcare to combat HAIs, but no less important are precautionary measures that can prevent the spread of pathogens with acquired resistance to antibiotics in hospitals.…”
Section: Introductionmentioning
confidence: 99%